CLINICAL SUPERVISION AS AN ALTERNATIVE TO IMPROVE THE CAPABILITY OF CLASS III TEACHERS IN THEMATIC LEARNING IN TAMBUSAI UTARA DISTRICT - Khairuddin Khairuddin (STKIP Rokania Pasir Pangaraian, 2021)
This research is motivated by the results of academic supervision in the second semester of the 2019/2020 school year for 36 low-grade teachers in 11 target schools in implementing thematic learning. This is due to (1) the lack of assistance and guidance from school supervisors, (2) the implementation of academic supervision has not used appropriate supervision techniques, (3) the teacher's low understanding of using themes to relate several subjects, (4) the lack of teachers in developing network’s themes, and (5) in developing the syllabus and lesson plans, it does not begin with mapping of basic competencies. The problem studied is the low ability of teachers in thematic learning in class III and the purpose of this research is to improve third grade teacher's ability in thematic learning. This research is school action research conducted in 2 cycles. Each cycle refers to on the objectives and research problems. Actions in cycle 2 depend on the results of reflection in the previous cycle and so on until the expected goals are achieved. The results of this study turned out to be a significant increase in the ability of third grade teachers in thematic learning, namely from 41.3 or 58.8% category enough in the cycle 1, to 55.7 or 78.4% in cycle 2 thus there is an increase of 13.8 or 19.6%. The implementation of supervision with clinical supervision techniques changes the teacher's view from feeling afraid when being supervised to feeling happy and comfortable because clinical supervision aims to provide services and assistance